Genotype-specific responses in Atlantic salmon (Salmo salar) subject to dietary fish oil replacement by vegetable oil: a liver transcriptomic analysis - Morais, Sofia; Pratoomyot, Jarunan; Taggart, John; Bron, James; Guy, Derrick R; Bell, J Gordon; Tocher, Douglas R (BMC Genomics, 2011)
Background: Expansion of aquaculture is seriously limited by reductions in fish oil (FO) supply for aquafeeds. Terrestrial alternatives such as vegetable oils (VO) have been investigated and recently a strategy combining genetic selection with changes in diet formulations has been proposed to meet growing demands for aquaculture products. This study investigates the influence of genotype on transcriptomic responses to sustainable feeds in Atlantic salmon. Results: A microarray analysis was performed to investigate the liver transcriptome of two family groups selected according to their estimated breeding values (EBVs) for flesh lipid content, 'Lean' or 'Fat', fed diets containing either FO or a VO blend. Diet principally affected metabolism genes, mainly of lipid and carbohydrate, followed by immune response genes. Genotype had a much lower impact on metabolism-related genes and affected mostly signalling pathways. Replacement of dietary FO by VO caused an up-regulation of long-chain polyunsaturated fatty acid biosynthesis, but there was a clear genotype effect as fatty acyl elongase (elovl2) was only up-regulated and desaturases (D5fad and D6fad) showed a higher magnitude of response in Lean fish, which was reflected in liver fatty acid composition. Fatty acid synthase (FAS) was also up-regulated by VO and the effect was independent of genotype. Genetic background of the fish clearly affected regulation of lipid metabolism, as PPARα and PPARβ were down-regulated by the VO diet only in Lean fish, while in Fat salmon SREBP-1 expression was up-regulated by VO. In addition, all three genes had a lower expression in the Lean family group than in the Fat, when fed VO. Differences in muscle adiposity between family groups may have been caused by higher levels of hepatic fatty acid and glycerophospholipid synthesis in the Fat fish, as indicated by the expression of FAS, 1- acyl-sn-glycerol-3-phosphate acyltransferase and lipid phosphate phosphohydrolase 2. Conclusions: This study has identified metabolic pathways and ...